answer:

x+y-z=-44x-y+z=-6-x+5y-4z=1

262002 solve using matrices by elimination x+y-z=-52x-y+z=2-x+4y-3z=1 x+y-z=-52x-y+z=2-x+4y-3z=1

262003 solve using matrices by elimination x+y-z=-53x-y+z=-7-x+5y-4z=1 x+y-z=-53x-y+z=-7-x+5y-4z=1

262004 solve using matrices by elimination x+y-z=-32x-y+z=6-x+5y-4z=1 x+y-z=-32x-y+z=6-x+5y-4z=1

262005 solve using matrices by elimination x+y-z=-34x-y+z=13-x+5y-4z=1 x+y-z=-34x-y+z=13-x+5y-4z=1

262006 solve using matrices by elimination x+y-z=-1x-2y+z=7-2x+2y+4z=-4 x+y-z=-1x-2y+z=7-2x+2y+4z=-4

262007 solve using matrices by elimination 4x+y-z=47x+7y-6z=7 4x+y-z=47x+7y-6z=7

262008 solve using matrices by elimination 4x+8y=126x+12y=18 4x+8y=126x+12y=18

262009 solve using matrices by elimination 4x+5y=58x+10y=10 4x+5y=58x+10y=10

262010 solve using matrices by elimination 4x-12y=-16x+4y=4 4x-12y=-16x+4y=4

262011 solve using matrices by elimination 4x-16y=20-x+4y=5 4x-16y=20-x+4y=5

262012 solve using matrices by elimination -4x-2y=-12 4x+8y=-24 -4x-2y=-12 4x+8y=-24

262013 solve using matrices by elimination 4x-2y-3z=-112x-2y+6z=44y+3z=3 4x-2y-3z=-112x-2y+6z=44y+3z=3

262014 solve using matrices by elimination 4x-4y+4z=-44x+y-2z=5-3x-3y-4z=-16 4x-4y+4z=-44x+y-2z=5-3x-3y-4z=-16

262015 solve using matrices by elimination 4x-5y=1-8x+10y=-2 4x-5y=1-8x+10y=-2

262016 solve using matrices by elimination 4x-5y=3-8x+10y=-6 4x-5y=3-8x+10y=-6

262017 solve using matrices by elimination 4x-5y=4-8x+10y=-8 4x-5y=4-8x+10y=-8

262018 solve using matrices by elimination 5x+3y=32x-6y=30 5x+3y=32x-6y=30

262019 solve using matrices by elimination 5x+2y+z=-11 , 2x-3y-z=17 , 7x-y=12 5x+2y+z=-11 , 2x-3y-z=17 , 7x-y=12

262020 solve using matrices by elimination 4x-7y=-5-6x+5y=2 4x-7y=-5-6x+5y=2

262021 solve using matrices by elimination 4x-y+3z=12 x+4y+6z=-32 5x+3y+9z=20 4x-y+3z=12 x+4y+6z=-32 5x+3y+9z=20

262022 solve using matrices by elimination 6x-y-9z=54x+y-z=68x+y-8z=8 6x-y-9z=54x+y-z=68x+y-8z=8

262023 solve using matrices by elimination 6x+7y=-1612x+14y=-18 6x+7y=-1612x+14y=-18

262024 solve using matrices by elimination 6x+7y=67x+8y=5 6x+7y=67x+8y=5

262025 solve using matrices by elimination -7x+5y=43-9x+2y=42 -7x+5y=43-9x+2y=42

step-by-step explanation: